2017
DOI: 10.1002/adem.201700267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Torsion Route on the Microstructure and Mechanical Properties of Extruded AZ31 Rods

Abstract: Torsion deformation is an effective and simple technique to tailor the mechanical properties of Mg alloys. In this study, the influences of torsion route on microstructure and mechanical properties of AZ31 rods are investigated. The maximum torsion angle is set as 180 and the two-pass torsion at different torsion routes, twice-successive unidirectional torsion (T A ) and reciprocating torsion (T B ), is used to process the Mg alloy rods. It is found that the mechanical properties and yield asymmetry are very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…For Mg alloys, cold deformation can also arouse textural change and arouse texture hardening/softening [83,102]. Pre-deformation via slip deformation at a low-strain generally exhibits little influence on texture.…”
Section: Strengthening Mechanism Via Combined Use Of Cold Deformatmentioning
confidence: 99%
“…For Mg alloys, cold deformation can also arouse textural change and arouse texture hardening/softening [83,102]. Pre-deformation via slip deformation at a low-strain generally exhibits little influence on texture.…”
Section: Strengthening Mechanism Via Combined Use Of Cold Deformatmentioning
confidence: 99%
“…In recent years, Guo et al [8,16] have pointed out that torsion processing is not only a common material fatigue test method, but an efficient strategy to prepare a quantitative controlled gradient structure for rod-shaped parts. High-performance gradient structural materials can be prepared by controlling torsion path [14,17], torsion speed [18], and the combined annealing process [19,20]. Recently, we have developed a new method to introduce a gradient of martensite phase in austenitic steels, with a volume fraction increasing from core to surface, via free-end torsion (FET).…”
Section: Introductionmentioning
confidence: 99%
“…Hagihara et al [12] confirmed that the (0001) [11,12,13,14,15,16,17,18,19,20] basal dislocation slip is the main deformation mode of the LPSO phase. Xu et al [10] reported that when the loading direction of compression deformation was basically parallel to the base plane of the LPSO phase, the base slip was difficult to open due to having a low Schmid factor.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [17] studied the Swift effect on the tensile and compressive yield asymmetry of AZ31 magnesium alloy by torsional deformation. The results of Shu et al [18] show that different torsional paths can improve the tensile and compressive asymmetry, and may enhance the aging strengthening effect of AZ91 alloy. At present, there are few studies on the torsional deformation behavior of rare earth magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%